2017
DOI: 10.9734/bjemt/2017/33536
|View full text |Cite
|
Sign up to set email alerts
|

External Market Conditions that Affect Cost of Tendering in Public Institutions: Evidence from Ghana

Abstract: The study examined the external factors or low visibility factors that affect the accuracy of pre-tender estimate among building contractors of public institutions in the Brong and Ashanti Regions of Ghan a. The study was structured within the framework of descriptive research approach. The study was conducted between August, 2016 and March, 2017. Building contractors who had registered with the various public institutions within the Ashanti and Brong Ahafo Regions of Ghana constituted the population of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Kissi et al [56] identified major economic indicators that influence the forecast of tender price indices in buildings as composite CPI, PPI, currency exchange rate, GDP, and interest rate and suggested the need for critical examination of the extent of economic impact on pricing of building contracts. Amoateng and Osei [57] considered currency exchange rate, CPI, and the general economic conditions as the major exogenous factors influence tendering in public institutions. Amoah-Mensah [58] in developing local price adjustment factor for the building industry in West Africa considered exchange rate and changes in price of crude oil as major factors.…”
Section: Review Of Literature On Exogenous Economic Factorsmentioning
confidence: 99%
“…Kissi et al [56] identified major economic indicators that influence the forecast of tender price indices in buildings as composite CPI, PPI, currency exchange rate, GDP, and interest rate and suggested the need for critical examination of the extent of economic impact on pricing of building contracts. Amoateng and Osei [57] considered currency exchange rate, CPI, and the general economic conditions as the major exogenous factors influence tendering in public institutions. Amoah-Mensah [58] in developing local price adjustment factor for the building industry in West Africa considered exchange rate and changes in price of crude oil as major factors.…”
Section: Review Of Literature On Exogenous Economic Factorsmentioning
confidence: 99%